(3LQjeI GdJgQjH GdefXe ddgLQI ZjQ GdeTQhYI (B: s (3eY OQGSI JWHjbjI Ydi GdLeghQjI GdjefjI (B/ s - (3eMeO MehO eSGYO CHh ZGfes; (3eMehO eMeO SdjeGf cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3ef CLd JhVjM LQjeI JgQjH GdgLQI ZjQ GdTQYjI abO JfGhdJ gPI GdOQGSI eaghe GdgLQI GdOhdjI GdTQYjI hZjQ GdTQYjI, Ke JYQVJ dHjGf eGgjI LQjeI JgQjH GdegGLQjf aj GdbhGfjf GdOhdjI ef MjK JYQja GdLQjeI, hCSHGHgG, hCQcGfgG, hGdJYGedGJ GdeGdjI ajgG, h OhQ GdaSGO aj GfJTGQ gPI GdLQjeI, hGdJejjR HjfgG hHjf LQjeI GdEJLGQ HGdHTQ, deSGFdI fWGb JgQjH GdegGLQjf ef MjK CWQGag GdaGYdI, hCfeGW GdJgQjH hWQbI hGdefGWb GdJj jJe ajgG, ceG JfGhdJ GdQSGdI HMK GdBdjI GdOhdjI ddJYGhf aj ehGLgI JgQjH GdegGLQjf, hCKQgG Ydi GdegGLQjf GdegQHjf, aJfGhdJ GdJYGhf GdOhdj aj ehGLgI LQjeI JgQjH GdegGLQjf heGjJYdb Hg ef GJaGbjGJ OhdjI JeJ aj gPG GdTCf, Ke JYQVJ dHMK hJaUjd Mbhb GdGfSGf PGJ GdUdI aj bVGjG JgQjH GdegGLQjf , hJhVjM CSGSgG aj GdbGfhf GdOhdj, haj GdaUd GdJWHjbj hGdCNjQ dgPI GdOQGSI NUUg GdHGMK ddOQGSI GdJWHjbjI Ydi GdJgQjH GdefXe ddgLQI ZjQ GdeTQhYI aj GdLeghQjI CdjefjI, Ke aj fgGjI GdOQGSI GSJYQVJ GdOQGSI YOO ef GdfJGFL hGdJhUjGJ GdgGeI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B569-606.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdgLQI ZjQ GdTQYjIs; (3JgQjH GdegGLQjfs; (3ecGaMI ZSd GdCehGds; (3GdGJLGQ HGdHTQs; (3GddGLFs; (3GdGYGOI GdbSQjIs; (3GdJYGhf GdOhdjs; (3Mbhb GdGfSGfs; (3GdgLQI ZjQ GdeTQhYI aj Gdjefs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs